2018
DOI: 10.1109/tbme.2018.2814597
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Detection Using Frequency Domain Fluorescent Lifetime Measurements

Abstract: The FD-FLIM system can provide a high throughput diagnostic technique that does not require a physician.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…Consistent with our previous studies, findings of this FD-FLT study, as presented using boxplots ( Figure 3A); reveal that the infected samples present pronounced prolonged median FLTs with wider distribution (range of 2.30-4.54 ns) in respect to the controls (range 2.30-2.92 ns) [30]. Nonetheless, as the median FLT values and their distributions overlap between the bacterial and viral infected samples, this approach is insufficient to detect the type of infection.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our previous studies, findings of this FD-FLT study, as presented using boxplots ( Figure 3A); reveal that the infected samples present pronounced prolonged median FLTs with wider distribution (range of 2.30-4.54 ns) in respect to the controls (range 2.30-2.92 ns) [30]. Nonetheless, as the median FLT values and their distributions overlap between the bacterial and viral infected samples, this approach is insufficient to detect the type of infection.…”
Section: Resultssupporting
confidence: 92%
“…Simulation I represents a general case of three widely spaced FLTs. Simulation II represents common closely FLT values, which correspond to FLTs of DAPI bound to DNA of leukocytes in different situations .…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decades, the ORR has been widely used as an intrinsic indicator of redox states in cells and tissues [26][27][28]. In addition to redox ratio imaging, fluorescence lifetime imaging microscopy (FLIM) has also been used for mapping of cellular metabolism [29][30][31] and detection of pathogens [32]. We found that the ORR of BAT increases significantly after NE injection in mice, which is correlated with the temperature rise in BAT induced by thermogenesis [14].…”
Section: Introductionmentioning
confidence: 86%
“…This may provide opportunities to investigate the metabolic characteristics of beige fat at subcellular resolution in vivo, which has not been conducted in live animal model. In addition to redox ratio imaging, fluorescence lifetime imaging microscopy (FLIM) has also been used for mapping of cellular metabolism [29][30][31] and detection of pathogens [32]. NADH and FAD exhibit distinct fluorescence lifetimes (FLTs) in free and protein-bound forms, and the free-to-bound ratios of NADH or FAD can be used to discriminate different cellular metabolic states [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…FLI can be measured in frequency domain (frequency modulated techniques) and in time domain (timeresolved techniques) 18,19 . Many time-domain FLI techniques use time-correlated single-photon counting (TCSPC), a technique generally used in scanning confocal set-ups 20 (with exceptions, see e.g.…”
Section: Introductionmentioning
confidence: 99%